Teachers entrepreneurial pedagogical content knowledge roles in human resource development - Sipon, Merhayati; Lope Pihie, Zaidatol Akmaliah; Abdul Rahman, Fadzilah; Abdul Manaf, Umi Kalthom (New Millennium Discoveries, 2015)
Among one of the strategic plan that's being enforced by Malaysia in generating a creative and innovative human resource is by strengthening the entrepreneurship education. This effort is in line with the aspiration of Malaysia’s Innovation Human Capital Development Plan, which emphasized entrepreneurship as an added value to alumnus employability, hence brought forth more quality human resources. However, the Global Entrepreneurship Monitor (GEM) showed that there is a gradual decrease in the entrepreneurial intention indicator among Malaysians since 2012. The decrement is a negative indication in Malaysia’s effort to achieve its vision of becoming a developed nation by the year 2020. Accordingly, Malaysia needs to reassess the planning and development of human resources. This paper discusses the views on the enforcement of teacher’s pedagogical content knowledge in entrepreneurship education which can contribute to the success of the human capital development in Malaysia.